Quality and Change in Teacher Education Western and Chinese Perspectives - Lee, John Chi-kin; Day, Christopher (Professional Learning and Development in Schools and Higher Education, 2016)
How teachers may be better educated for a changing global world is a challenge that faces many systems of education worldwide. This book addresses key issues of quality and change in teacher education in the context of the new public management achievement agendas which are permeating teacher education structures, cultures and programmes and the work of teacher educators internationally. Graduate schools of education in the United States and the UK, for example, are making fundamental changes in the structures, courses, programs and faculties that prepare beginning teachers each year. Drawing upon examples from the United States, United Kingdom, China, Hong Kong, Australia and elsewhere, its authors provide a unique critical overview of emerging themes and challenges of raising the quality of teaching and the quality of student learning outcomes. They suggest possible ways forward for teachers, teacher educators, researchers and policy-makers as they seek to raise the quality of teaching and student outcomes whilst sustaining their moral purposes and values of equity, inclusion and social justice. Taken together, the chapters contain informed, critical discussions of "normal education" and "teacher education" of "professional standards", "4+2/+1" post-degree training, "PGDE versus BEd", integration of subject specializations and professional education. Each one provides new visions of the teacher as a professional and to cultivate high quality teachers in the West and the Greater China region. For all those interested in issues of quality, change and forward movement in teacher education in contexts of policy led reform, this is a must read.